If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 3 = 0 Reorder the terms: 3 + 8y = 0 Solving 3 + 8y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 8y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 8y = 0 + -3 8y = 0 + -3 Combine like terms: 0 + -3 = -3 8y = -3 Divide each side by '8'. y = -0.375 Simplifying y = -0.375
| 12y=16y | | 6(x-6)=9 | | 4=xsquare-7 | | 2/3x+3=3/4 | | 10x-2y=-8 | | 4e^2x+2=16 | | (4/4)((-7)-(-9)) | | y=8x-119 | | 2-2(-8z+2)=-3(8z+9)-1 | | 5xsquare+500=844.45 | | 2(6x-4)=8(2x-1) | | m=7.5+-1.5n | | 5x^2+9=10-4x^2 | | 7(x-2)=5(8-2x)+17x | | 7x-6y=-46 | | 7x+5x-9x+5=13 | | X^2-1=4-x^2/4 | | 6ab-9a+4ab-5a= | | 5(x-4)=-7(8+2x)+19x | | 5x-(1/4)=3x-(5/4) | | 20=10x-35 | | 8x+2=36 | | 5x^2+8=35+2x^2 | | 90=4t+19t | | z=x-77.5/11.6 | | 1.8+n=1.4 | | (-2.3)*(-4.6)*3= | | t+11=11 | | -6x-8=-4x+2 | | 2r+10=13 | | 3x^2=18+x^2 | | 4-(x/5)=16 |